The Preference Survey Module: A Validated Instrument for Measuring Risk, Time, and Social Preferences - Falk, Armin; Becker, Anke; Dohmen, Thomas; Huffman, David; Sunde, Uwe (Management Science, 2023)
Incentivized choice experiments are a key approach to measuring preferences in economics but are also costly. Survey measures are a low-cost alternative but can suffer from additional forms of measurement error due to their hypothetical nature. This paper seeks to leverage the strengths of both approaches by proposing a new survey module on risk aversion, time discounting, trust, altruism, positive and negative reciprocity, in which survey items are selected based on ability to predict choices in corresponding, incentivized experiments. The methodology and results provided in the paper can also potentially provide a model for researchers who have specific requirements and want to design their own modules. This paper was accepted by Yan Chen, behavioral economics and decision analysis. Funding: The project received funding from the European Research Council under the European Union’s Seventh Framework Programme (FP7-2007-2013) [Grant 209214]. A. Falk and T. Dohmen acknowledge funding from the Deutsche Forschungsgemeinschaft (German Research Foundation) [Grant CRC TR 224 (Project A01)] and Germany’s Excellence Strategy [Grant EXC 2126/1-390838866]. Supplemental Material: Data and the online appendices are available at https://doi.org/10.1287/mnsc.2022.4455 .